To solve the equation using the quadratic formula, first rewrite it in standard form:
x^2 + 7x + 10 = 0
Now we can identify the coefficients a = 1, b = 7, and c = 10 to plug into the quadratic formula:
x = (-b ± √(b^2 - 4ac)) / 2a
x = (-7 ± √(7^2 - 4*1*10)) / (2*1)
x = (-7 ± √(49 - 40)) / 2
x = (-7 ± √9) / 2
x = (-7 ± 3) / 2
Now we have two possible solutions:
x = (-7 + 3) / 2 = -4/2 = -2
x = (-7 - 3) / 2 = -10/2 = -5
Therefore, the solutions are x = -2 and x = -5.
Use the quadratic formula to solve the equation. If necessary, round to the nearest hundredth.
x2+10=-7x
(1 point)
0 x=2,5
0 x=-2,5
•x=2,-5
•x=-2,-5
1 answer